Fine structure of critical opalescence spectra - Sushko, M.Ya. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The effect of the 1.5-scattering mechanism on the time and temperature behavior of the electric field autocorrelation function for the light wave scattered from fluids has been studied for the case where the order-parameter fluctuations obey the diffusion-like kinetics with spatially-dependent kinetic coefficient. The leading contributions to the relevant static correlation functions of the order-parameter fluctuations were obtained by using the Ginzburg–Landau model with a cubic term, and then evaluated with the use of the Gaussian uncoupling for many-point correlation functions and the Ornstein–Zernicke form for the pair correlation function. It is shown that the presence of the 1.5-scattering effects in the overall scattering pattern may be detected in the form of a small but noticeable deviation from exponential decay of the total electric field autocorrelation function registered experimentally near the critical point. Obtained with the standard methods of analysis, the effective halfwidth of the corresponding spectrum can reveal a stronger temperature dependence and a multiplicative renormalization as compared to the halfwidth of the spectrum of the pair correlator.